(untitled) - Pommerville, Jeffrey C. (Sudbury, Mass., 2004)
Including the latest disease data and statistics, new material on emerging disease outbreaks, and expanded use of concept maps, and may other pedagogical features. With an inviting Learning Design format and Study Smart notes to students, Alcamo's Fundamentals of Microbiology
Keywords: Microbiology,Vi sinh vật